2018
DOI: 10.1177/2059204318769639
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the role of music in the neurodevelopment of autism spectrum disorder

Abstract: Music has played a prominent role in the clinical and research literature on autism spectrum disorder (ASD) in regard to diagnosis, therapy, and behavioral observations of exceptional artistic abilities in this population. Music as therapy for ASD has traditionally focused on social interaction, communication skills, and social-emotional behaviors. However, recently, there has been an increased research focus on the role of motor and attention functions as part of the hallmark features of ASD, which may have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 210 publications
(273 reference statements)
4
62
0
2
Order By: Relevance
“…Individuals with ASD have a unique profile of strengths amid limitations, which can be harnessed to design treatment paradigms that improve functional outcomes 94 . Given their universal appeal, intrinsic reward value and ability to modify brain and behaviour, musical activities have been proposed as a potential strength-based rehabilitation tool for ASD 22 , 36 , 95 . In the current trial, we demonstrate that 8–12 weeks of music intervention can indeed alter intrinsic brain connectivity and improve parent-reported outcomes in social communication and FQoL in school-age children with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with ASD have a unique profile of strengths amid limitations, which can be harnessed to design treatment paradigms that improve functional outcomes 94 . Given their universal appeal, intrinsic reward value and ability to modify brain and behaviour, musical activities have been proposed as a potential strength-based rehabilitation tool for ASD 22 , 36 , 95 . In the current trial, we demonstrate that 8–12 weeks of music intervention can indeed alter intrinsic brain connectivity and improve parent-reported outcomes in social communication and FQoL in school-age children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the impact of music on social functioning and brain connectivity, alongside atypicalities in these areas in ASD, music-based activities may restore altered brain connectivity and social difficulties in ASD. Synthesizing findings from previous research, two possible mechanisms for such music-induced neuroplasticity and its impact on social functioning may be proposed: 32 , 36 , 44 , 45 (1) top–down reward-based cortical modulation to reinforce learning of non-musical behaviours such as social interactions through the intrinsic reward value of music, (2) bottom–up sensorimotor integration through sound and auditory–motor entrainment of neural networks through synchronization leading to modulation of atypical sensory processing, which in turn may improve social communication 41 , 46 . Our goal was to investigate whether music-based interventions can indeed alter spontaneous rsfMRI signals, leading to improved functioning in ASD based on one of the above hypotheses.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…More recently, neuroimaging studies have shown that participating in musical activities engages a multimodal network of brain regions involved in hearing, movement, emotion, pleasure and memory (47)(48)(49), thus allowing transfer of music-related therapeutic effects to non-musical domains (50-54) through structural and functional brain changes (55)(56)(57)(58). However, a direct link between effects of music interventions and changes in the brain is yet to be demonstrated in autism (59,60), and was our aim here.…”
Section: Introductionmentioning
confidence: 98%
“…These results from Heaton et al (1999) suggest that emotional valence cues are equivalently available for ASD individuals and typically developing individuals (Molnar-Szakacs and Heaton 2012). Music is also successfully employed as a therapeutic tool amongst this population (Geretsegger et al 2014;Janzen and Thaut 2018;Sharda et al 2018). Forms of music therapy have been reported to aid people with severe ASD significantly improve in musical skill in different ways, such as short/long melody recall and rhythm reproduction (Boso et al 2007).…”
Section: Introductionmentioning
confidence: 99%